2019
DOI: 10.2138/rmg.2019.85.14
|View full text |Cite
|
Sign up to set email alerts
|

RTM for Waste Repositories

Abstract: ILLW in clay formation Clay-atmospheric O 2 Construction phase (disposal cell) Bentonite handling and emplacement Construction phase (disposal cell) Concrete-atmospheric CO 2 Construction and ventilation phase (wells, tunnel)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 270 publications
(280 reference statements)
0
13
0
Order By: Relevance
“…Appropriate numerical simulations using highly developed and augmented reactive transport codes are an essential ingredient of the longterm performance assessment of nuclear waste repositories. 28,29,[60][61][62][63][64][65] A serious weakness in the current knowledge base is the lack of reliable temperature dependent thermodynamic information for the most important chemical species and chemical reactions involved. 31,[66][67][68] The elaboration of a complete chemical thermodynamic database 27,28,69,70 is mandatory if we desire to bring the results of such simulations in agreement with the experimental information.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate numerical simulations using highly developed and augmented reactive transport codes are an essential ingredient of the longterm performance assessment of nuclear waste repositories. 28,29,[60][61][62][63][64][65] A serious weakness in the current knowledge base is the lack of reliable temperature dependent thermodynamic information for the most important chemical species and chemical reactions involved. 31,[66][67][68] The elaboration of a complete chemical thermodynamic database 27,28,69,70 is mandatory if we desire to bring the results of such simulations in agreement with the experimental information.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling in ACED is based on so-called continuum modeling, in which the flow and transport of solutes (and possible gases) by diffusion and advection are coupled with thermodynamic and kinetic models to represent the geochemical state. Such models are typically called coupled reactive transport models [6], and although they have already been available for several decades, their recent capabilities now allow them to handle complex environmental and engineering problems, including radioactive waste disposal [7,8]. Beside the reactive transport codes themselves, and the variety of geochemical processes under different conditions (e.g.…”
Section: Assessment Of the Chemical Evolution At Disposal Cell Scale ...mentioning
confidence: 99%
“…Arguably, one of the most significant achievements in reactive transport analysis in recent years has been the application to multiphase systems, including soils and the deep vadose zone where mostly water and air coexist (Dwivedi et al 2019;Arora et al 2019, both this volume), and the deep subsurface where other fluids and gases may be present (e.g., oil, gas, steam). It is well beyond the scope of this contribution to review these, but some discussion can be found in Sin and Corvisier (2019) and in Bildstein et al (2019), both this volume. This is a challenging topic because of the presence of different phases, each of which has its own transport and chemical properties, and because of the complex, typically time-dependent interfaces between the phases.…”
Section: Multiphase Reactive Systemsmentioning
confidence: 99%